The Relation Between Preference for Predictability and Autistic Traits. Issue 7 (4th December 2019) - Goris, Judith; Brass, Marcel; Cambier, Charlotte; Delplanque, Jeroen; Wiersema, Jan R.; Braem, Senne
Abstract : A common idea about individuals with autism spectrum disorder (ASD) is that they have an above‐average preference for predictability and sameness. However, surprisingly little research has gone toward this core symptom, and some studies suggest the preference for predictability in ASD might be less general than commonly assumed. Here, we investigated this important symptom of ASD using three different paradigms, which allowed us to measure preference for predictability under well‐controlled experimental conditions. Specifically, we used a dimensional approach by investigating correlations between autistic traits (as measured with the Autism‐Spectrum Quotient and Social Responsiveness Scale in a neurotypical population) and the scores on three different tasks. The "music preference" task assessed preferences for tone sequences that varied in predictability. The "perceptual fluency" task required participants to evaluate stimuli that were preceded by a similar versus dissimilar subliminally presented prime. The "gambling" task presented four decks of cards that had equal outcome probabilities but varied in predictability. We observed positive correlations between autistic traits and a preference for predictability in both the music preference and perceptual fluency task. We did not find our hypothesized correlation with gambling behavior but did observe a post hoc correlation showing that participants with more autistic traits were faster to choose the predictable deck. Together, these findings show that a relation between autistic traits and preference for predictability can be observed in a standardized lab environment, and should be considered an important first step toward a better, more mechanistic understanding of insistence on sameness in ASD. Autism Res 2020, 13 : 1144‐1154. © 2019 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: A core symptom of autism spectrum disorder (ASD) is a strong preference for predictability, but little research has gone toward it. We show that neurotypical adults with more autistic traits have stronger preferences for predictable tunes, evaluate images that can be predicted as more beautiful, and are faster in choosing a gambling option resulting in predictable reward. These results offer the first important evidence that insistence on sameness in ASD can be studied in controlled lab settings.